Maternal sociodemographic and health behaviours associated with adiposity in infants as measured by air displacement plethysmography - Bennett, Annemarie E.; Kearney, John M. (Early human development, 2020)
Identifying modifiable factors associated with body fat in infancy may improve health outcomes. Few studies have examined factors associated with percentage body fat calculated using air displacement plethysmography, a gold standard technique. To investigate maternal sociodemographic and health behaviour characteristics associated with percentage body fat in offspring at birth. Observational cross-sectional study in which the body composition of term infants was measured by air displacement plethysmography during the hospital stay after birth. One-hundred-and-ninety-six women and their term (37–42 weeks) infants. Associations between infant body composition and maternal sociodemographic and health characteristics. One-hundred-and-ninety-six women (41.8% primiparous) participated. Mean percentage body fat among infants (51.5% female) was 10.3 ± 3.7. Percentage body fat was significantly (p < 0.001) higher in infants born to women with an obese or overweight body mass index (BMI), when compared to infants born to women with a healthy BMI (12.1 ± 4.0, 11.1 ± 3.1, and 9.2 ± 3.7, respectively). A significant positive correlation (r = 0.294) was observed, with the percentage body fat of infants born to women with an overweight or obese BMI being 17.1% and 23.9% higher, respectively, than that of infants born to women with a healthy weight BMI. Percentage body fat was lower in infants born to primiparous women (p = 0.011) and women of low social class (p = 0.003). Infants born to women with an overweight or obese pre-pregnancy BMI had significantly higher mean percentage body fat when compared to infants born to women with a healthy pre-pregnancy BMI. Research into approaches that promote a healthy BMI in advance of pregnancy is warranted. •Identifying factors associated with neonatal adiposity may improve health outcomes.•Percentage body fat was measured at birth using air displacement plethysmography.•Women with pre-pregnancy overweight had infants with higher percentage body fat.•Interventions that promote a healthy body mass index before pregnancy are needed.